THE EFFECT OF THIEVES STRATEGY ON THE STUDENTS’ READING COMPREHENSION THROUGH ONLINE LEARNING MODEL - Kharisma Karunia Ilahi (Graduate Program, University of Islam Malang, 2021)
The aim of this study was to measure the effectiveness of the THIEVES strategy on the reading comprehension achievement of students at Junior High School seventh grade students. This research was done in five meetings. One meeting for pretest, three meetings for treatment, and one more for posttest. In this study, researcher used quantitative methods with pre-experimental research design in which this study was only conducted in one research class. The subjects was 20 students taken from the seventh grade of Private Junior High School in East Java, Indonesia. This study was conducted during the Covid 19 pandemic so it was conducted online. Face-to-face learning in this study was conducted online using zoom and WhatsApp. In data collection, by presenting a multiple choice test consisting of 20 items for each test, the researcher performed a pre-test and posttest. The data was analyzed using SPSSS to calculate paired sample t-test.The results of statistical calculations obtained the mean score of pre-test 55.50 and 68.25 for the post-test. The t value 12.074. Based on the